PENGARUH EKSTRAKURIKULER PRAMUKA TERHADAP KARAKTER KEPEMIMPINAN PESERTA DIDIK DI SMA NEGERI 1 INDRALAYA - Meidelasari; Sri Artati Waluyati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of Scout extracurricular activities on the leadership character of students at SMA Negeri 1 Indralaya. The leadership character is examined through five indicators: relationship-building, agility and adaptability, digital competence, broad insight, and acting as an agent of change. Employing a quantitative approach with a descriptive method, data were collected through questionnaires, interviews, and documentation. The population comprised 34 Scout members, all of whom were included as samples using a saturated sampling technique. The simple linear regression analysis revealed a positive and significant influence of Scout extracurricular activities on students' leadership character, with a coefficient of determination (R²) of 0,420 or 42%. This indicates that 42% of the variation in students' leadership character can be explained by their participation in Scout activities, while the remaining 58% is influenced by other factors. These findings suggest that Scout activities such as marching drills, routine training, and camping effectively foster practical and contextually relevant leadership values in students' daily lives.